Images of the urban religious landscape: Gen Z seek out the sacred in the city. Issue 2 (4th May 2022) - Samson, Maxim G. M.; Leichty, James G.
ABSTRACT: In spite of growing attention among geographers to the diversity of religious spaces, young adults' perceptions of such sites and their relevance in contemporary society remain relatively under-researched. In response, this article focuses on Generation Z undergraduates' conceptualizations of religious space and engagement with broader questions pertaining to the sacralization of urban sites. The students identified a wide range of urban sites beyond places of worship as religious—including murals, storefronts, sidewalk decorations and tattoos – and in the process revealed the pervasiveness of religion and religious spaces, thereby uncovering some new possible directions for geographical inquiry. Moreover, they shared their attitudes regarding contested issues like gentrification and the commodification of religious symbols, and in relation the place of religion in contemporary society. By gaining such a glimpse into the worldviews of Generation Z, we may develop a better understanding of the ways that they perceive religious space and its relevance to urban life.